2008
DOI: 10.1242/dev.017350
|View full text |Cite
|
Sign up to set email alerts
|

Directional migration of neural crest cells in vivo is regulated by Syndecan-4/Rac1 and non-canonical Wnt signaling/RhoA

Abstract: Directed cell migration is crucial for development, but most of our current knowledge is derived from in vitro studies. We analyzed how neural crest (NC) cells migrate in the direction of their target during embryonic development. We show that the proteoglycan Syndecan-4 (Syn4) is expressed in the migrating neural crest of Xenopus and zebrafish embryos. Loss-of-function studies using an antisense morpholino against syn4 show that this molecule is required for NC migration, but not for NC induction. Inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
303
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(336 citation statements)
references
References 52 publications
23
303
1
1
Order By: Relevance
“…However, neither dominant active nor dominant negative Cdc42 influenced the heterotypic CIL of NIH3T3 cells in our system. Similarly, Cdc42 does not appear to be involved in the polarization and protrusion formation of NC cells [38].…”
Section: Discussionmentioning
confidence: 96%
“…However, neither dominant active nor dominant negative Cdc42 influenced the heterotypic CIL of NIH3T3 cells in our system. Similarly, Cdc42 does not appear to be involved in the polarization and protrusion formation of NC cells [38].…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10] The neural crest is an embryonic population of cells that are specified at the border between the neural plate and the epidermis. 11 Upon induction neural crest cells undergo an epithelial to mesenchymal transition, 12 detach from the neural tube and migrate following defined pathways that eventually allow them to colonize almost the entire embryo.…”
mentioning
confidence: 99%
“…More importantly, we have been able to show that the same molecular machinery controls directional migration in vivo. 9,10 One of the key factors that controls directional migration of NC cells is the Planar Cell Polarity (PCP) or non-canonical Wnt signaling pathway. 9,10,16 PCP signaling was first described in Drosophila, where a number of mutations were identified that disrupt the formation of bristles and hairs on the adult cuticle.…”
mentioning
confidence: 99%
See 2 more Smart Citations